The Mass Murder of the European Jews and the Concept of ‘Genocide’ in the Nuremberg Trials: Reassessing Raphaël Lemkin’s Impact - Alexa Stiller (Genocide Studies and Prevention: An International Journal, 2019)
Nuremberg’s prosecutors prominently used Lemkin’s genocide concept. They also dealt in detail with the mass murder of Europe’s Jews. However, for them ‘genocide’ and the Holocaust were not congruent. They used different definitions of Lemkin’s concept and interpreted the relationship between the mass murder of the European Jews and the entire mass violence of the Nazis differently. Lemkin had little influence on the application of his concept in the Nuremberg trials between 1945 and 1949. The implementation of the 1948 United Nations Genocide Convention put an end to the broad use of the original concept from 1944. Although both Lemkin and the prosecutors in the Nuremberg trials went through a similar development in the early post-war years to underline the special character of the Nazi mass murder of the European Jews. The development paths were different, but led to a similar result.